Sorghum: variability of nutrients and bioactive compounds and their heat processing stability - Cardoso, Leandro de Morais (2014)
Sorghum is the fifth most produced cereal in the world. This cereal is a source of nutrients and bioactive compounds, especially 3- deoxyanthocyanidins, tannins, and polycosanols, which beneficially modulate parameters related to non-communicable diseases. Sorghum needs to be processed prior to use for human consumption, which may change its antioxidant compounds. This study aimed to evaluate the variability of nutrients and bioactive compounds in sorghum (Sorghum bicolor L.) and their stability to extrusion and dry heat in a conventional oven. One hundred sorghum genotypes were selected from a core collection with high genetic variability from Embrapa Maize and Sorghum (Sete Lagoas, MG, Brazil) and the content of carotenoid and vitamin E were analyzed by high performance liquid chromatography (HPLC) with diode array detector. The genetic variability of carotenoids and tocochromanols in 100 sorghum genotypes were assessed by Tocher’s clustering technique. The one hundred sorghum genotypes showed high variability in tocochromanol content (280.7-2,962.4 μg/100g in wet basis) and 23% of the genotypes were classified as source of vitamin E. Also, the total carotenoid content varied from 2.12 to 85.46 μg/100g in the one hundred sorghum genotypes. According to the genetic variability for carotenoids and tocochromanols, the 100 genotypes were divided into seven groups genetically distinct from each other. From 100 genotypes, three sorghum genotypes were selected (genotype SC319; genotype B.DLO357 and genotype SC391) and submitted to three types of treatment: F1) Raw flour: grains ground in a micro-rotor analytical mill (850 μm); F2) Dry heat in a conventional oven/milling (Oven/ milling): whole grains subjected to dry heat in a conventional oven (DHCO) (121 ° 25 min) and C, subsequently, ground in a micro-rotor analytical mill (850 μm); F3) Extrusion/milling: grains extruded in a co-rotating twin-screw. The grains of the three processed genotypes were characterized according to the content of carotenoids, 3-deoxianthocyanidins, flavones and flavanones, that were determined by HPLC with diode array detector; the vitamin E content and the degree of polymerization of proanthocyanidins, that were analyzed by HPLC with fluorescence detection; and the total phenolics compounds and the antioxidant activity, that were determined by spectrophotometry. Data normality on the stability of antioxidant compounds was assessed using the Shapiro-Wilk test and the differences between treatments were evaluated by ANOVA, followed by Duncan test to compare the treatment averages, at 5% probability. The retention of the total tocochromanols and α-tocopherol equivalent decreased after extrusion (69.1-84.8% and 52.4-85.0%, respectively) but increased after DHCO (106.8-114.7% and 109.9-115.8%, respectively). Sorghum carotenoids were sensitive to extrusion (30.7-37.1%) and DHCO (58.6-79.2%). The content of flavanones and flavones decreased after extrusion (100%) and DHCO (31.7 to 61.6%). The 3-DXAs were stable in DHCO, but were susceptible to extrusion (70.7 to 93.9%). Proanthocyanidins were identified only in the genotype SC391 and reduced after both treatments (DHCO: 39.2% and extrusion: 52.1%). Phenols decreased in the genotype SC319 submitted to DHCO (8.3%) and in all extruded genotypes (13.6-14.9%). The DHCO increased the antioxidant capacity in all genotypes, whereas extrusion reduced the antioxidant capacity in only two genotypes. In conclusion, the tocochromanols profile in sorghum varied widely and the genotypes presented high genetic variability for carotenoids and tocochromanols. Sorghum was a source of tocochromanols, which increased after DHCO and decreased after extrusion. The carotenoid content in sorghum decreased after DHCO and extrusion. The differential stability of the major flavonoids in sorghum was observed under DHCO and extrusion treatments, implying that different processing techniques can be selected to minimize losses of bioactive polyphenols in sorghum depending on the flavonoid composition.